PENINGKATAN MINAT BELAJAR MATEMATIKA KELAS IV MELALUI ALAT PERAGA LAYANG-LAYANG - Warsito, Warsito (Elementary School Teacher and Education (PGSD), Faculty of Teacher Training and Education, 2019)
This aimed research to increased interest in learning mathematics with kite media. This research was classroom action research. The subjects of this study were IVC grade students of MI Negeri 6 Sukoharjo in the Academic Year 2019/2020 with a total of 30 students. Data collection techniques were by distributing questionnaire of interest in learning and observation to get valid data. The analysis technique used was a quantitative descriptive. Data management on mathematics learning interests by collecting scores from the learning interest scale, then converting. the results of research concluded that the use of kite media can increased interest in learning mathematics in class IVC MI N 6 Sukoharjo. This can be seen from the results of filling out the questionnaire starting from pre-cycle with a minimum category of enough 15 students then increasing to 23 students in the first cycle, then in the second cycle can be increased again to 30 students. From the direct teacher's observationed of the learning process also proved four indicators of student interest have emerged / appeared.